(untitled) (Trabalho & Educação, 2018)
This study aims to verify the conception of teachers from a Secondary Technical Course in Business Administration on the issue of integrating basic education curriculum to professional education curriculum. The paper presents a documentary research in the legislation on the offer of technical courses integrated to secondary education in Brazil, rescuing the period between 2004 and 2016. It also presents a theoretical research on the theme of curriculum integration of professional and basic education. The research is an exploratory study and the data collection was performed through an electronic questionnaire applied to the teachers of the course. The results, although evaluated positively, point to the immediate imperative of constructive dialogues on how to make a curriculum integration that contributes to the formation of competent citizens for life and work. The posture and performance of teachers are confirmed as fundamental pillars for the success of integrated technical courses. ___ Este estudo objetiva verificar a concepção dos docentes atuantes em um Curso Técnico em Administração Integrado ao Ensino Médio sobre a integração curricular da educação básica com a educação profissional. O trabalho conta com uma pesquisa documental na legislação sobre a oferta de cursos técnicos integrados ao ensino médio no Brasil, resgatando o período compreendido entre 2004 e 2016; além de pesquisa teórica sobre o tema integração curricular da educação profissional com a educação básica. A pesquisa se configura como estudo exploratório e a coleta de dados foi realizada por meio de questionário eletrônico aplicado aos docentes do curso. Os resultados, embora avaliados positivamente, apontam o imperativo imediato de diálogos construtivos sobre como fazer uma integração curricular que contribua para a formação de cidadãos competentes para a vida e para o trabalho. A postura e atuação docentes se confirmam como pilares fundamentais para o êxito dos cursos técnicos integrados.